2014
DOI: 10.1101/009191
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inference of Gorilla demographic and selective history from whole genome sequence data

Abstract: Although population-level genomic sequence data have been gathered extensively for humans, similar data from our closest living relatives are just beginning to emerge. Examination of genomic variation within great apes offers many opportunities to increase our understanding of the forces that have differentially shaped the evolutionary history of hominid taxa. Here, we expand upon the work of the Great Ape Genome Project by analyzing medium to high coverage whole-genome sequences from 14 western lowland gorill… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 55 publications
5
23
0
Order By: Relevance
“…We included the P. leucopus demographic history into our analysis and found 0.019% of the sequenced loci to contain SFS patterns indicative of selective sweeps. This rate is in line with other studies that reported that 0.5% of regions in domesticated rice (Wang et al, 2014), 0.02% of loci in black cottonwood (Zhou, Bawa, & Holliday, 2014) and 0.02% of the gorilla genome (McManus et al, 2014) show evidence of selective sweeps or hitchhiking.…”
Section: Population Genomic Summary Statisticssupporting
confidence: 92%
“…We included the P. leucopus demographic history into our analysis and found 0.019% of the sequenced loci to contain SFS patterns indicative of selective sweeps. This rate is in line with other studies that reported that 0.5% of regions in domesticated rice (Wang et al, 2014), 0.02% of loci in black cottonwood (Zhou, Bawa, & Holliday, 2014) and 0.02% of the gorilla genome (McManus et al, 2014) show evidence of selective sweeps or hitchhiking.…”
Section: Population Genomic Summary Statisticssupporting
confidence: 92%
“…As g‐phocs models the coalescent process without incorporating recombination, it assumes no recombination within loci, and free recombination between loci. Following several other studies (Choi et al., ; Gronau et al., ; Hung et al., ; McManus et al., ), we picked 1 kb loci separated by at least 50 kb. Following (Gronau et al., ), loci were selected not to contain the following classes of sites within the O. niloticus reference genome—that is, rather than being simply masked, these sites were not allowed to occur in input loci: (a) hard‐masked (N) or soft‐masked (lowercase bases) sites in the publicly available genome assembly; (b) sites that were identified to be prone to ambiguous read mapping using the program SNPable (Li, , using k = 50 and r = 0.5 and excluding rankings 0 and 1); and (c) any site within an exon or <500 bp from an exon boundary.…”
Section: Methodsmentioning
confidence: 99%
“…Western gorillas are estimated to have diverged from eastern gorillas approximately 261 Kya, with some gene flow continuing between the populations until between approximately 77-150 Kya 31,32 .…”
Section: A High Frequency Snp In Gorilla Oas1 Controls Catalytic Outputmentioning
confidence: 99%